3-Hydroxyisobutyrate Dehydrogenase Is Involved in Both, Valine and Isoleucine Degradation in Arabidopsis thaliana . Issue 1 (13th July 2017) - Schertl, Peter; Danne, Lennart; Braun, Hans-Peter
Abstract : 3-Hydroxyisobutyrate dehydrogenase, an enzyme of the branched-chain amino acid breakdown pathway, is involved in valine and isoleucine but not in leucine degradation in Arabidopsis. Abstract: In plants, amino acid catabolism is especially relevant in metabolic stress situations (e.g. limited carbohydrate availability during extended darkness). Under these conditions, amino acids are used as alternative substrates for respiration. Complete oxidation of the branched-chain amino acids (BCAA s) leucine, isoleucine (Ile), and valine (Val) in the mitochondria efficiently allows the formation of ATP by oxidative phosphorylation. However, the metabolic pathways for BCAA breakdown are largely unknown so far in plants. A systematic search for Arabidopsis ( Arabidopsis thaliana ) genes encoding proteins resembling enzymes involved in BCAA catabolism in animals, fungi, and bacteria as well as proteomic analyses of mitochondrial fractions from Arabidopsis allowed the identification of a putative 3-hydroxyisobutyrate dehydrogenase, AtHDH1 (At4g20930), involved in Val degradation. Systematic substrate screening analyses revealed that the protein uses 3-hydroxyisobutyrate but additionally 3-hydroxypropionate as substrates. This points to a role of the enzyme not only in Val but possibly also in Ile metabolism. At4g20930 knockdown plants were characterized to test this conclusion. Root toxicity assays revealed increased root growth inhibition of the mutants if cultivated in the presence of Val or Ile but not in the presence of leucine. We conclude that AtHDH1 has a dual role in BCAA metabolism in plants.